Interactive Meaning in Visual Images: A Multimodal Analysis of the English for Nusantara EFL Textbook - Soni Ardian Fasya; Arif Suryo Priyatmojo (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2026)
This qualitative study employs a multimodal discourse analysis framework developed by Kress and van Leeuwen to examine how visual images in the English for Nusantara Kelas IX textbook construct interactive meaning for ninth-grade EFL learners in Indonesia. The analysis focuses on dimensions of interactive meaning: social distance, perspective, gaze, and modality. A total of 31 images depicting human participants were analyzed. The findings reveal that most images are represented through medium shots (77.41%) and oblique angles (96.78%), tending to position learners primarily as observers rather than symbolically involved participants. Additionally, the use of simplified and stylized visual modality emphasizes visual simplicity while potentially reducing contextual immersion. These findings suggest that while the textbook’s visual design may foreground instructional clarity and content delivery, it may provide fewer visual cues for interpersonal involvement and participatory positioning. The study offers analytically informed recommendations for textbook developers and educators to adopt a more balanced visual grammar that integrates both observational and participatory framing to enhance learner engagement.